2006
DOI: 10.1038/nature04592
|View full text |Cite
|
Sign up to set email alerts
|

STED microscopy reveals that synaptotagmin remains clustered after synaptic vesicle exocytosis

Abstract: Synaptic transmission is mediated by neurotransmitters that are stored in synaptic vesicles and released by exocytosis upon activation. The vesicle membrane is then retrieved by endocytosis, and synaptic vesicles are regenerated and re-filled with neurotransmitter. Although many aspects of vesicle recycling are understood, the fate of the vesicles after fusion is still unclear. Do their components diffuse on the plasma membrane, or do they remain together? This question has been difficult to answer because syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
818
1
9

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,076 publications
(842 citation statements)
references
References 24 publications
14
818
1
9
Order By: Relevance
“…These proteins are mobile and intermix with newly exocytosed synaptic vesicle proteins 44,45 . By contrast, super-resolution stimulated emission depletion (STED) microscopy (BOX 4) has suggested that newly exocytosed synaptic vesicle proteins are clustered at the plasma membrane 46 . This apparent contradiction could be explained by differences between pHluorin-tagged synaptic vesicle membrane proteins and their native endogenous counterparts 47 .…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins are mobile and intermix with newly exocytosed synaptic vesicle proteins 44,45 . By contrast, super-resolution stimulated emission depletion (STED) microscopy (BOX 4) has suggested that newly exocytosed synaptic vesicle proteins are clustered at the plasma membrane 46 . This apparent contradiction could be explained by differences between pHluorin-tagged synaptic vesicle membrane proteins and their native endogenous counterparts 47 .…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
“…Conflicting light-microscopic data regarding the mobility and state of clustering of newly exocytosed proteins [44][45][46][47] (FIG. 4b) may be explained by a model assuming that synaptic vesicle proteins initially decluster, but then undergo rapid reclustering (FIG.…”
Section: Super-resolution Light Microscopic Techniquesmentioning
confidence: 99%
“…Sample preparation: Primary cultures of neonatal rat hippocampal neurons were prepared as previously described [32]. Synaptotagmin was selectively labeled on the cell surface via monoclonal mouse antibodies (604.2) and Atto 647N-labeled goat anti-mouse Fab fragments as described elsewhere [21].…”
Section: Methodsmentioning
confidence: 99%
“…Synaptotagmin [33,34], a key protein in exocytosis, is a major constituent of synaptic vesicles [35] and is known to form clusters after exocytosis of neurotransmitter vesicles [32]. We imaged fluorescently la- beled synaptotagmin within axons of living cultured neurons at video-rate (28 frames per second) and a spatial resolution of 65 nm.…”
Section: Pulsed Sted Versus Confocal Microscopymentioning
confidence: 99%
“…By contriving the STED beam to have a minimum intensity (preferably zero) at the centre, the point spread function (PSF) of the microscope is effectively narrowed below the diffraction limit. This is often realised by propagating the STED beam through a suitable phase retarding plate [23,24] to impart a helical phase profile and achieve a so called "doughnut" shaped PSF at the focus of the objective lens. This approach is fundamentally limited only by the available power in the depletion beam and has realised lateral resolutions down tĂ” 6 nm [25] imaging NV centers in polycrystalline CVD diamond.…”
Section: Biophotonicsmentioning
confidence: 99%